The proposal of permanent education in the formation of dentists in std/hiv/aids - Maria de Fátima Nunes; Cláudio Rodrigues Leles; Márcio Florentino Pereira; Renata Tolêdo Alves; Philip Sidney Pacheco Badiz (Faculdade de Medicina de Botucatu (Unesp), 2008)
The objective of this work is to report the experience of the "Project for the formation of dentists as facilitators of Permanent Education in Health in the area of STD/HIV/AIDS" developed in partnerships with the National Program of STD/AIDS, the Technical Area of Oral Health of the Ministry of Health, Public Universities and Municipal and State Secretaries of Health. The objective of the program was to capacitate dentists of the public health system in Brazilian states and cities to provide integral and humanized attendance for people living with HIV/AIDS. The methodology of choice for the form of teams of facilitators was Permanent Education in Health through semi-presential courses focusing on the problematization of local and professional realities. Thus, seeking to construct a process of education to modify and reorient the hegemonic dental practice, strengthening the process of attendance and management and the partnerships, guaranteeing the sustainability of the actions in the states and cities.